Pharmacokinetics of Psilocybin: A Systematic Review - Shakila Meshkat; Huda Al-Shamali; Argyrios Perivolaris; Trusha Tullu; Richard J. Zeifman; Yanbo Zhang; Lisa Burback; Olga Winkler; Andrew Greenshaw; Muhammad Ishrat Husain; Amy C. Reichelt; Eric Vermetten; et al. (Pharmaceutics)
Background: Psilocybin has shown promise in therapeutic applications for mental disorders. Understanding the pharmacokinetics of psilocybin and its active metabolite psilocin is crucial for optimizing its clinical use and minimizing adverse effects. Methods: This systematic review involved a comprehensive search across MEDLINE, APA PsycINFO, and Embase databases, from inception to December 2024, identifying original studies that investigated the pharmacokinetics of psilocybin. Results: Fourteen studies met the inclusion criteria: eight laboratory-based and six clinical studies. Laboratory studies used animal models or in vitro systems, while clinical studies included 112 healthy human participants. Psilocybin is rapidly dephosphorylated to psilocin, which is absorbed with Tmax values ranging from 1.8 to 4 h following oral administration. Cmax varied dose-dependently, from 8.2 ± 2.8 ng/mL (plasma) to 871 ng/mL (urine). One study reported psilocin bioavailability at 52.7 ± 20%. The volume of distribution was extensive, ranging from 277 ± 92 L to 1016 L, suggesting significant tissue distribution. Psilocin metabolism is primarily mediated by CYP2D6 and CYP3A4, with secondary contributions from monoamine oxidase A. It undergoes further hepatic biotransformation into 4-hydroxyindole-3-acetic acid and 4-hydroxytryptophol. Elimination half-life varied across studies, ranging from 1.5 to 4 h. Conclusions: Psilocybin pharmacokinetics demonstrate significant variability based on dosage, route, and species. CYP enzymes play a critical role in its metabolism, highlighting the potential for drug–drug interactions. These findings underscore the importance of further research to elucidate psilocybin’s pharmacokinetic profile, which is assessed in vivo by its active metabolite psilocin.